The Influence of Medicare Home Health Payment Incentives: Does Payer Source Matter? - David C. Grabowski; David G. Stevenson; Haiden A. Huskamp; Nancy L. Keating (SAGE Publishing, 2006)
During the late 1990s, the U.S. government instituted an interim payment system (IPS) to constrain Medicare home health care expenditures. Previous research has focused largely on the implications of the IPS for Medicare patients; this study broadens the analysis to consider patients with other payer sources. Using the National Home and Hospice Care Survey, we found similar effects of the IPS across payer types. Specifically, the IPS was associated with a decrease in care for the sickest patients, less agency assistance with activities of daily living, and shorter length of use. However, these changes did not translate into worse discharge outcomes.